Pulse repetition-rate effect on the intensity inside a femtosecond laser filament in air - Yin, Fukang; Long, Juan; Liu, Yaoxiang; Wei, Yingxia; Zhu, Bin; Zhou, Kainan; Wang, Tie-Jun; Leng, Yuxin; Li, Ruxin (High power laser science and engineering, 2023)
As intense, ultrashort, kHz-repetition-rate laser systems become commercially available, pulse cumulative effects are critical for laser filament-based applications. In this work, the pulse repetition-rate effect on femtosecond laser filamentation in air was investigated both numerically and experimentally. The pulse repetition-rate effect has negligible influence at the leading edge of the filament. Clear intensity enhancement from a high-repetition pulse is observed at the peak and tailing edge of the laser filament. As the repetition rate of the laser pulses increases from 100 to 1000 Hz, the length of the filament extends and the intensity inside the filament increases. A physical picture based on the pulse repetition-rate dependent ‘low-density hole’ effect on filamentation is proposed to explain the obtained results well.